Kontribusi Aktivitas Pendidikan Rekreasi terhadap Kesehatan Mental Mahasiswa Semester Akhir Program Studi Pendidikan Jasmani FKIP Universitas PGRI Jombang - Yunarta, Arsika; Andrianto, Joan Rhobi (SPRINTER: Jurnal Ilmu Olahraga, 2025)
This study aims to determine the contribution of recreational education activities to the mental health of final-semester students in the Physical Education Study Program, Faculty of Teacher Training and Education (FKIP), PGRI University of Jombang. The research was motivated by the increasing academic and psychological pressure experienced by students approaching graduation, which requires recreational activities to balance their mental well-being. This study employed a quantitative approach with a correlational design. The population consisted of all final-semester students in the Physical Education Study Program, with a sample of 60 respondents selected using a proportional random sampling technique. The research instrument was a Likert-scale questionnaire that had been tested for validity and reliability. Data were analyzed using simple linear regression, showing that recreational education activities contributed 47.8% to students’ mental health (r = 0.691; p < 0.05). The findings indicate that higher participation in recreational education activities is associated with better mental health among students. The study concludes that recreational education plays a significant role in maintaining the psychological balance of final-semester students and should be continuously integrated into campus wellness programs.